Analysis of the Mindfulness Approach in View of the Learning Readiness of Class V Students at SDN 15 Singkawang - Rahmadi; Mertika; Kamaruddin Kamaruddin (LPPM Universitas PGRI Semarang, 2025)
The mindfulness approach can be an option used by teachers to develop students' potential. This study aims to1) describe the application of the mindfulness approach in the learning of class V students at SDN 15 Singkawang, 2) describe the learning readiness of class V students at SDN 15 Singkawang, 3) describe the analysis of the mindfulness approach in terms of the learning readiness of class V students at SDN 15 Singkawang. The type of research used is case study research and qualitative research design. The research was conducted at SDN 15 Singkawang. The research subjects were 23 class V students. Research data was taken using observation, interview and documentation techniques. Then the data is analyzed through data reduction, data display, and conclusion drawing/verification. From the research results it was found that: 1) The mindfulness approach taken by teachers to students is very varied and this provides a positive response from students, such as several rules and activities that students carry out every time they come to school or enter class to start learning; 2) Students' learning readiness as seen from the four indicators shows that students are ready to learn. These four indicators show that the mental readiness of students who feel happy, the situational readiness of students who understand that the classroom atmosphere is comfortable for learning, the readiness of their goals when they come to school, and the physical readiness of students who are healthy and ready to focus on learning; 3) Overall, the mindfulness approach in terms of students' learning readiness shows that children are ready to learn with feelings of joy and healthy physical condition, a comfortable learning atmosphere and high learning goals.